A simple, selective, and sensitive gas chromatography–mass spectrometry method for the analysis of five process‐related impurities in atenolol bulk drug and capsule formulations. Issue 15 (28th June 2017) - Reddy, Ambavaram Vijaya Bhaskar; Yusop, Zulkifli; Jaafar, Jafariah; Bin Aris, Azmi; Abdul Majid, Zaiton
Abstract : An extremely sensitive and simple gas chromatography with mass spectrometry method was developed and completely validated for the analysis of five process‐related impurities, viz., 4‐hydroxy‐l ‐phenylglycine, 4‐hydroxyphenylacetonitrile, 4‐hydroxyphenylacetic acid, methyl‐4‐hydroxyphenylacetate, and 2‐[4‐{(2 RS )‐2‐hydroxy‐3‐[(1‐methylethyl)amino]propoxy}phenyl]acetonitrile, in atenolol. The separation of impurities was accomplished on a BPX‐5 column with dimensions of 50 m × 0.25 mm i.d. and 0.25 μm film thickness. The method validation was performed following International Conference on Harmonisation guidelines in which the method was capable to quantitate 4‐hydroxy‐l ‐phenylglycine, 4‐hydroxyphenylacetonitrile, and 4‐hydroxyphenylacetic acid at 0.3 ppm, and methyl‐4‐hydroxyphenylacetate and 2‐[4‐{(2 RS )‐2‐hydroxy‐3‐[(1‐methylethyl)amino]propoxy}phenyl]acetonitrile at 0.35 ppm with respect to 10 mg/mL of atenolol. The method was linear over the concentration range of 0.3–10 ppm for 4‐hydroxy‐l ‐phenylglycine, 4‐hydroxyphenylacetonitrile, and 4‐hydroxyphenylacetic acid, and 0.35–10 ppm for methyl‐4‐hydroxyphenylacetate and 2‐[4‐{(2 RS )‐2‐hydroxy‐3‐[(1‐methylethyl)amino]propoxy}phenyl]acetonitrile. The correlation coefficient in each case was found ≥0.998. The repeatability and recovery values were acceptable, and found between 89.38% and 105.60% for all five impurities under optimized operating conditions. The method developed here is simple, selective, and sensitive with apparently better resolution than the reported methods. Hence, the method is a straightforward and good quality control tool for the quantitation of selected impurities at trace concentrations in atenolol.